ANALISIS KARAKTERISTIK DAN MOTIVASI PETANI DALAM USAHA TANI KEDELAI DI KECAMATAN LEUWIDAMAR - Mubarok, Robby; Agustina Rusadi, Widya; Triguna, Rizki; Meilani, Yusi; Fitriyah, Sri; Rizkyta Ananda, Lintang (CV. Lafadz Jaya, 2025)
Soybean is a vital source of vegetable protein and used in food and animal feed industries. However, soybean production and land area in Indonesia have been declining due to the influx of cheap imported soybeans, which lowers local prices and discourages farmers from cultivating soybeans. This research aims to identify the factors influencing the motivations and characteristics of soybean farmers in Leuwidamar District, Lebak, Banten. Using a survey method and random sampling, 72 out of 251 farmers were selected. The results show that the farmers are mostly in their productive age, with limited land, low farming experience, small capital, basic education, and many dependents. Key motivating factors include age, farming experience, land tenure, income, availability of agricultural inputs, and extension services. Farmers value hands-on experience over formal education, and both farmers with few and many dependents have similar motivations to cultivate soybeans, driven by government programs, income generation, skill improvement, and external encouragement from relatives, neighbors, and agricultural extension workers.